Preparing for the New Jerusalem : Seeing the Light at Last - 20160731 frey50 (Authorhouse Bloomington, IN, 2011)
Carol Briggs is a retired school teacher whose story may be very much like yours, to a point: self sufficient, getting a degree, then a career, marriage and family. Her story may vary in that she taught overseas in teh Bahamas, canary Islands, and New Delhi, India and brought home a 'live' souvenir from each country. She has never written a book and never planned to - until the Lord woke her up hearly one morning at 4:30 A.M. and said clearly, "Type this title on your computer, PREPARING FOR THE NEW JERUSALEM."
Keywords: Christianity. -- Religious life styles